Ilm Ad-Dalalah fi At-Turats Al-Lughawi Al-‘Arabi An-Nigeri Baina Al-Ashalah wa Al-Hadatsah - Abdul Ghani Abimbula Abdus Salam; Tsalis Abdul Karim (UIN Maulana Malik Ibrahim Malang, 2019)
علم الدلالة يهتم بدراسة معاني المفردات اللغوية، وله أهمية ٌقصوى في مجال صناعة المعاجم اللغوية والترجمة والتعريب، ودراسة الصوتيات وبنية الكلمات واشتقاقاتها، وكل ما هو من شأنه عناية بأساليب تراكيب اللغة البشرية، ودراية ما تكنه ألفاظها من أسرار دلالية، لمواكبة مستجدات الحضارة الإنسانية. وعليه تتقصى هذه المقالة خطوات سلفنا من العلماء والدارسين وجهودهم المبذولة تجاه علم الدلالة في التراث العربي النيجيري، لمعرفة قيمه اللغوية فيما بين الأصالة والحداثة. وذلك تأكيدا للجيل الناشئ من أن علمائنا اللغويين في هذا الوطن قد خلفوا لنا تراثا لغويا عربيا نيجيريا في علم الدلالة الأصيل.The significance of linguistics concerns with lexicography, translation and arabization, including the study of Phonology, the structure of words and its derivatives. All of them minds the methods of human language structures enhancing tangible pace of development in human civilization. This article explores the steps taken by our scholars and their efforts towards the Semantics of the Arab-Nigerian heritage, in order to discover its linguistic values between originality and modernity. This is an affirmation to the younger generation that the linguists have left Arab-Arabic heritage in the original Semantics. This article tries to examine the presence of Semantics in the Arab-Nigerian heritage, between its old and modern concept through the efforts of Nigerian linguists in Semantics. It deals with the concept of significance in Arab heritage, and the presentation of Linguistics on the ancient Arabic and modern linguists, exploring the efforts of local scholars in the Semantics of Arab-Nigerian heritage.